Computational Thinking Using MathWay Software On Algebra Material In The Era Of Technology-Based Learning - Riska Yulidar; Siti Lailiyah; Lisanul Uswah Sadieda (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
Computational thinking ability is one of the important skills in the 21st century. The MathWay application offers interactive features that support mathematics learning, especially in algebra material. This study aims to systematically review the existing literature related to the effectiveness of using MathWay on students' computational thinking skills. The research uses the Systematic Literature Review (SLR) method, with data collection techniques carried out by studying relevant literature related to computational thinking, MathWay applications, and algebra. The article selection process is carried out by formulating research questions, conducting systematic literature searches, applying inclusion and exclusion criteria, and analyzing and summarizing findings, followed by making conclusions. The analysis uses the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) diagram method, with four relevant scientific articles obtained. The results of the study indicate that the use of MathWay is effective in improving students' computational thinking skills, especially in problem solving and algorithmic thinking patterns.